Pengaruh Financial Literacy, Fintech, Dan Financial Behavior Terhadap Kualitas Laporan Keuangan Umkm Dalam Transformasi Digital Ekonomi - Wahyuningsih, Sri; Banjarnahor, Haposan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The digital economic transformation has significantly impacted business management, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the influence of financial literacy, fintech, and financial behavior on the quality of financial statements in MSMEs amid the digital transformation era. The research was conducted on MSME actors in Batu Aji District, Batam City, with a total of 64 respondents. A quantitative approach was employed, using questionnaires for data collection. Data were analyzed using multiple linear regression with the assistance of SPSS version 31. The results indicate that financial literacy, fintech, and financial behavior have a positive and significant effect on the quality of financial statements, both partially and simultaneously. These findings highlight the importance of these three factors in supporting accountable and transparent financial management in the digital era. The implication of this study emphasizes the need to enhance the capacity of MSME human resources in financial literacy and technology adoption to improve the quality of financial information.